2015
DOI: 10.1007/s00266-015-0583-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transconjunctival Blepharoplasty on Margin Reflex Distance 2

Abstract: This journal requires that the authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…On the subcutaneous plane, this is the area where the junction of the palpebral-orbicularis oculi muscle and superior border of the malar fat pad meet. On the submuscular plane, it is fixed to the orbital rim by the orbital retaining ligaments, the protruded orbital fat placed on the ligaments, and the SOOF located beneath the ligaments [8][9][10]. LCJ descends gradually with aging, because the vertical length of the lower lid is increased by skin and muscle laxity, protruded orbital fat, and resorption of bone [2].…”
Section: Discussionmentioning
confidence: 99%
“…On the subcutaneous plane, this is the area where the junction of the palpebral-orbicularis oculi muscle and superior border of the malar fat pad meet. On the submuscular plane, it is fixed to the orbital rim by the orbital retaining ligaments, the protruded orbital fat placed on the ligaments, and the SOOF located beneath the ligaments [8][9][10]. LCJ descends gradually with aging, because the vertical length of the lower lid is increased by skin and muscle laxity, protruded orbital fat, and resorption of bone [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference in lower eyelid position after either technique ( p >0.5) [ 11 ]. Segal et al [ 12 ] reported that transconjunctival blepharoplasty did not induce lid retraction but rather elevated the lower eyelid in a majority of patients using MRD 2 measurement. Elevation of the lower eyelid can reduce or eliminate scleral show inferiorly, providing further cosmetic advantages.…”
Section: Discussionmentioning
confidence: 99%
“…3 The ratio (R) of the values of MRD2/WTW was used to compensate for differences in scale inherent in photography; therefore the R reflects a "calculated" MRD2. 8 R was collected from all 74 eyes. It was averaged between the 3 different values collected by the 3 clinicians and then compared pre (R1) and post (R2) operatively to evaluate the efficacy of the muscular flap in preserving lower eyelid position after transcutaneous blepharoplasty.…”
Section: Exclusion Criteria Included: History Of Dry Eye Abnormal Snmentioning
confidence: 99%